New Insights for Polyphenolic Compounds as Naturally Inspired Proteasome Inhibitors - Emanuela Marchese; Maria Eugenia Gallo Cantafio; Francesca Alessandra Ambrosio; Roberta Torcasio; Ilenia Valentino; Francesco Trapasso; Giuseppe Viglietto; Stefano Alcaro; Giosuè Costa; Nicola Amodio (MDPI AG, 2023)
Polyphenols, an important class of natural products, are widely distributed in plant-based foods. These compounds are endowed with several biological activities and exert protective effects in various physiopathological contexts, including cancer. We herein investigated novel potential mechanisms of action of polyphenols, focusing on the proteasome, which has emerged as an attractive therapeutic target in cancers such as multiple myeloma. We carried out a structure-based virtual screening study using the DrugBank database as a repository of FDA-approved polyphenolic molecules. Starting from 86 polyphenolic compounds, based on the theoretical binding affinity and the interactions established with key residues of the chymotrypsin binding site, we selected 2 promising candidates, namely Hesperidin and Diosmin. The further assessment of the biologic activity highlighted, for the first time, the capability of these two molecules to inhibit the β5-proteasome activity and to exert anti-tumor activity against proteasome inhibitor-sensitive or resistant multiple myeloma cell lines.